Metodologias ativas de ensino e aprendizagem no Programa de Ensino Integral (PEI): A percepção de professores de uma escola estadual em Sorocaba-SP - Sartori, Érika Garcia (Universidade Federal de São Carlos, 2023)
Active teaching and learning methodologies are being studied and widely disseminated as educational practices that seek to build meaningful and innovative learning for students. In the midst of perceived changes in society, the school also seeks to innovate in its methodologies and propose pedagogical practices that provide students with autonomy, responsibility, cooperation, among other skills necessary for the new social scenario. Based on these premises, this research aims to identify the perceptions of teachers regarding the use of active methodologies in the Integral Teaching Program (PEI), as well as the methodologies are innovative, this program is also a new teaching model and seeks to develop protagonists and autonomous students. In this search, the research methodology used was quantitative and qualitative, at the beginning some investigations and documental analyzes of the PEI were necessary, later, narrative interviews were carried out so that the teachers working in the PEI could discuss their experiences and perceptions and, in the last step, a comparative analysis with the results of the participating school in the research at SARESP and the notes of the interviewed teachers. In the narrative interviews, the teachers reported about the confluence of their trajectories with the active methodologies, how they have observed the students' learning about the use of these differentiated methodologies, the difficulties and potentialities perceived throughout this process, the influence of the active methodologies on the external results that the school is evaluated and, lastly, the outstanding experiences with these innovative educational practices. The results have shown that there is a deficiency in continued formation education for teachers to be able to use these methodologies in an adequate, safe and efficient way, as in some moments of the narrative interviews the teachers demonstrated that they believe in the potential of active methodologies, but there is insecurity to use them. On the other hand, the quantitative results of the students in the SARESP external evaluation were not affected by the use of active methodologies and still showed a satisfactory evolution. This fact is directly linked to the perceptions demonstrated in the teachers narrative interviews, in which they reported the positive contribution of the active methodologies in the process of teaching and learning.
Active teaching and learning methodologies in the Integral Teaching Program (PEI): The perception of teachers at a state school in Sorocaba-SP
Keywords: Active methodologies; Metodologias ativas; Comprehensive Education Program; Teachers perception; Teacher training; Programa de Ensino Integral; Percepção dos professores; Formação de professores; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM